Internalisasi Nilai Antikorupsi dalam Pembentukan Karakter Pelajar Melalui Seminar Generasi Anti Korupsi - M. Yunasri Ridhoh; Indri Iswardhani; Sri Astuti Nasir; Nulthazam Sarah; Nur Fadilah Ayu Sandira (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
Corruption is a serious problem that leads to declining public trust, weakened governance, and hindered national development. Beyond economic losses, corruption also erodes moral values, ethics, and social justice within society. Therefore, corruption prevention efforts must be carried out systematically and sustainably, one of which is through the internalization of anti-corruption values at an early stage, particularly among students as future generations. This community service activity aimed to instill values of integrity, honesty, responsibility, and public ethics among students through the Anti-Corruption Generation Interactive Seminar, conducted in commemoration of International Anti-Corruption Day 2025. The activity involved approximately 150 junior and senior high school students in Makassar. The method employed was an interactive seminar implemented through material presentations and discussions between speakers and participants. The seminar materials emphasized an understanding of the dangers of corruption, its impacts on national and social life, and the strategic role of students in fostering an anti-corruption culture within schools and the wider community. The evaluation of the activity was conducted through observation of participant engagement and responses during the seminar. The results indicated an increase in students’ understanding and awareness of anti-corruption values, as well as the importance of integrity-oriented behavior in everyday life. This activity demonstrates that interactive seminars can serve as an effective approach to supporting students’ character development and strengthening preventive efforts against corruption.